1977
DOI: 10.1097/00004032-197705000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Accumulation and Elimination of Radiocesium by Naturally Contaminated Wood Ducks

Abstract: The accumulation of radiocesium was studied in hand-reared wood ducks which were released into a South Carolina swamp habitat which had been contaminated with production reactor effluents. The uptake of radiocesium by the ducks was described as:In pCi radiocesium/g live body weight = 0.36 + 0.18 (days). There was no effect of sex on uptake rate. The average estimated time required to attain practical equilibrium (0.90 Q,) was 17.3 days, with a range from 10.2 to 26.8 days. Ducks which were recaptured after att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 2 publications
3
17
0
Order By: Relevance
“…Positive correlations exist between the weight of the turtle and the elimination rate, and between weight and the concentration of the radionuclide in the turtle (initial body burden) (Peters and Brisbin 1988). No relationship was found be-tween elimination rate and the sex of the turtle (Peters and Brisbin 1988) which is consistent with that reported in birds (Fendley et al 1977).…”
Section: Radionuclidessupporting
confidence: 86%
See 1 more Smart Citation
“…Positive correlations exist between the weight of the turtle and the elimination rate, and between weight and the concentration of the radionuclide in the turtle (initial body burden) (Peters and Brisbin 1988). No relationship was found be-tween elimination rate and the sex of the turtle (Peters and Brisbin 1988) which is consistent with that reported in birds (Fendley et al 1977).…”
Section: Radionuclidessupporting
confidence: 86%
“…A comparison of the biological half-life of '37Cs in turtles to that in several other taxa revealed that it was greater than that for birds (Fendley et al 1977, Halford et al 1983 and wild mammals (Jenkins et al 1969). The longer retention of 13'Cs in turtles is consistent with the slower metabolic rate in the poikilothermic turtles.…”
Section: Radionuclidesmentioning
confidence: 99%
“…6.7 days was determined for older (7+days) little blue heron nestlings. This estimate is similar to estimates for other birds-wood ducks, Aix sponsa, .f = 5.6 days, range 3.2-9.3 days (Fe76), and blue jays, Cyanocitta cristutu, .f = 6.1 days, range 3.2-9.1 days (Le75). An assimilation rate of between 45 and 51% was estimated for the little blue heron.…”
Section: Resultssupporting
confidence: 84%
“…Soon after the nuclear accident that occurred at the Chernobyl Nuclear Power Plant (ChNPP) Cs content have been conducted for the whole body of animals, specifically, in fish (Hadderingh et al 1996;Belyaev 2001), birds (Brisbin et al 1973;Straney et al 1975;Levy et al 1976;Domby et al 1977;Fendley et al 1977;Craig et al 1979;Halford et al 1983;George et al 1990;Millard et al 1990;Kennamer et al 1993;Moss and Horrill 1996), and mammals (Richmond 1980). For this purpose, gamma spectrometric systems (or pulse counting devices) were developed and thoroughly calibrated, Sr and 137 Cs in-vivo measurements in the Chernobyl Exclusion Zone 3 which was a feasible but not necessarily easy task.…”
Section: Introductionmentioning
confidence: 99%